Retinal Nonperfusion in Proliferative Diabetic Retinopathy Before and After Panretinal Photocoagulation Assessed by Widefield OCT Angiography - Russell, Jonathan F.; Al-khersan, Hasenin; Shi, Yingying; Scott, Nathan L.; Hinkle, John W.; Fan, Kenneth C.; Lyu, Cancan; Feuer, William J.; Gregori, Giovanni; Rosenfeld, Philip J. (American journal of ophthalmology, 2020)
Widefield swept source optical coherence tomography angiography (WF SS-OCTA) imaging was compared with ultra-widefield (UWF) fluorescein angiography (FA) imaging to better understand changes in retinal nonperfusion before and after panretinal photocoagulation (PRP) in treatment-naïve eyes with proliferative diabetic retinopathy (PDR). Prospective, observational, consecutive case series. Participants with treatment-naïve PDR were imaged using the SS-OCTA 12- × 12-mm scan pattern at baseline and at 1 week, 1 month, and 3 months after PRP. UWF FA was obtained at baseline and 3 months after PRP. Selected eyes were imaged using 5 SS-OCTA 12- × 12-mm scans to create a posterior pole montage, and 5 eyes also underwent SS-OCTA imaging at 6 months and 1 year. Areas of retinal nonperfusion (RNP) were drawn independently by 2 masked graders, and analysis of variance (ANOVA) tests were used to compare areas of RNP over time. Main outcome measurements consisted of areas and boundaries of RNP visualized using WF SS-OCTA and UWF FA. From January 2018 through January 2019, WF SS-OCTA was performed on 20 eyes with treatment-naïve PDR from 15 patients. Areas of RNP identified on UWF FA images co-localized with RNP areas visualized on WF SS-OCTA images. There were no statistically significant changes in RNP area on WF SS-OCTA images through 3 months after PRP. Even eyes that were severely ischemic at baseline had no significant changes in RNP area 1 year after PRP. RNP in PDR can be identified at baseline and imaged serially after PRP using WF SS-OCTA. Retinal perfusion in PDR does not change significantly after PRP. The ability of WF SS-OCTA to longitudinally evaluate RNP areas provides additional justification for adopting WF SS-OCTA as the sole imaging modality for clinical management of PDR.